MSR-NLP Entry in BioNLP Shared Task 2011 - Quirk, Chris; Choudhury, Pallavi; Gamon, Michael; Vanderwende, Lucy (BioNLP Shared Task 2011 Workshop, Portland, Oregon, USA, 2011)
We describe the system from the Natural Language Processing group at Microsoft Research for the BioNLP 2011 Shared Task. The task focuses on event extraction, identifying structured and potentially nested events from unannotated text. Our approach follows a pipeline, first decorating text with syntactic information, then identifying the trigger words of complex events, and finally identifying the arguments of those events. The resulting system depends heavily on lexical and syntactic features. Therefore, we explored methods of maintaining ambiguities and improving the syntactic representations, making the lexical information less brittle through clustering, and of exploring novel feature combinations and feature reduction. The system ranked 4th in the GENIA task with an F-measure of 51.5%, and 3rd in the EPI task with an F-measure of 64.9%.